ANALISIS TATA HUBUNGAN KERJA PENGELOLAAN AREAL EKS HPH DALAM KESATUAN PENGELOLAAN HUTAN (KPH) DI PROVINSI JAMBI - Fazriyas, Fazriyas; Elwamendri, Elwamendri (Universitas Jambi, 2010)
Act (Act) No. 41, 1999 concerning state forestry forests is one determinant of life supporting systems and sources of welfare. During the first 20 years of forest management by concessions have many negative issues, especially forest destruction and many concession holders who cease to operate before the time runs out. They argument there are potential for wood that has been exhausted, and some of them not extend the operating license for the second time becouse forests have been heavily damaged and its potential continues to decline.Under these conditions, the Government in this case the Ministry of Forestry tried to look for the new format and issue a wide range of policies to create an optimal model of forest management. One of the policies issued by the government is the establishment of Forest Management Unit (FMU) in every function of forest area. Hereinafter abbreviated Forest Management Unit (FMU) is the smallest unit of forest management according to the principal functions , which can be managed efficiently and sustainably.Scientific papers about the analysis of governance relationships of ex HPH areas management in Jambi Province namely as a guide for local governments for implementation of a good institutional relationship that is consistent and harmonious between KPHP and IUPHHK units. While the goal of scientific writing in order to formulate a governance relationship between IUPHHK and KPHP units.In the implementation of sustainable production forest management, organization of production forest area is the Unitary Production Forest Management (KPHP) while for protected area is KPHL and for conservation areas is KPHK. In the former concession areas that do not have the license holder, KPHP duty are: (1) conduct forest management ex-concession area. (2) describe the national forest policy, provincial and district forestry sector to be implemented in the management of the former concession area in units of KPH. (3) implement forest management activities in their areas ranging from planning, organizing, implementation and supervision and control. (4) carry out monitoring and evaluation of the implementation of forest management activities in the areas of ex-HPH. (5) investment opportunities in the former concession area in order to support the achievement of objectives of forest management and (6) social construction in the community around KPH.